1974
DOI: 10.21273/jashs.99.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Differential Ability of Two Degenerative Sweet Corn Mutants to Stimulate Hybrid Vigor1

Abstract: A novel procedure was used to test for single locus heterosis in a substantially isogenic background in corn, (Zea mays L.). It was determined that the rd gene and its rdPw allele do not contribute to single locus heterosis for plant height. To explain why C30 induces heterosis in F1 hybrids, while ‘Pee Wee’ is relatively impotent, a hypothesis is proposed to the effect that C30 evolved from P39 by the addition of a mutagenic and heterotic duplicated chromosomal segment when Rd mutated to rd. In turn, ‘Pee Wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Variation was observed for ear weight, plant height, and ear height among the crosses, the highest yielding crosses involved C30. These results confirm previous results (Singleton, 1943; Lachman, 1972, 1974). Breeding experiments indicated that the differences in yield were due to a number of genetic factors (Singleton, 1948) Molecular data support this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Variation was observed for ear weight, plant height, and ear height among the crosses, the highest yielding crosses involved C30. These results confirm previous results (Singleton, 1943; Lachman, 1972, 1974). Breeding experiments indicated that the differences in yield were due to a number of genetic factors (Singleton, 1948) Molecular data support this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…previous results (Singleton, 1943;Lachman, 1972Lachman, , 1974. It is interesting to speculate about the role of transpos-Breeding experiments indicated that the differences in able elements in generating diversity among the strains.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations